Examining the relationship between selected parameters describing the body posture and mass and the height of the body and the place of living - Drzał-Grabiec, Justyna; Snela, Sławomir; Szczepanowska-Wołowiec, Beata; Bibrowicz, Karol (European Journal of Clinical and Experimental Medicine, 2012)
Introduction. The aim of the study is to compare parameters describing the body posture in children living in Podkarpacie and Śląsk. Material and methods. The study has been done in particular primary schools of Sub-Carphatian and Silesia regions. The 563 pupils of the three first school years have been examined, randomly chosen, whose parents gave a written agreement on that, including 278 boys (49,38%) and 285 girls (50,62%). Each examined pupil was set in 25 parameters describing the body posture using the photogrammetric method based on mora phenomenon. Results. Among 25 parameters, describing body posture, there are statistically significant differences, mainly in case of DCK, DKP, RKP, DLL, RLL, DELTA and KLL. Conclusions. 1. Parameters describing the posture are significantly different among examined groups. 2. Children from examined groups present statistical differences in a mass and the height of the body.